The Propagation Characteristics of Turbulent Expanding Flames of Methane/Hydrogen Blending Gas - Haoran Zhao; Chunmiao Yuan; Gang Li; Fuchao Tian (Energies)
In the present study, the effect of hydrogen addition on turbulent flame propagation characteristics is investigated in a fan-stirred combustion chamber. The turbulent burning velocities of methane/hydrogen mixture are determined over a wide range of hydrogen fractions, and four classical unified scaling models (the Zimont model, Gulder model, Schmidt model, and Peters model) are evaluated by the experimental data. The acceleration onset, cellular structure, and acceleration exponent of turbulent expanding flames are determined, and an empirical model of turbulent flame acceleration is proposed. The results indicate that turbulent burning velocity increases nonlinearly with the hydrogen addition, which is similar to that of laminar burning velocity. Turbulent flame acceleration weakens with the hydrogen addition, which is different from that of laminar flame acceleration. Turbulent flame acceleration is dominated by turbulent stretch, and flame intrinsic instability is negligible. Turbulent stretch reduces with hydrogen addition, because the interaction duration between turbulent vortexes and flamelets is shortened. The relative data and conclusions can provide useful reference for the model optimization and risk assessment of hydrogen-enriched gas explosion.